ANALISIS PENJATUHAN PUTUSAN OLEH HAKIM TERHADAP TINDAK PIDANA KORUPSI YANG TIDAK DIDAKWAKAN DALAM SURAT DAKWAAN DITINJAU MENURUT TEORI PROGRESIF (STUDI PUTUSAN NOMOR: 17/PID.SUS/TPK/2014/ PN.JKT.PST) - Kartika Cahyaningtyas (JURNAL SUMBER HUKUM, 2025)
This research examines and analyzes judges' decisions regarding corruption crimes not charged in the indictment. This is analyzed from the perspective of progressive theory. Progressive law teaches, "law is for humans and society, not law for law." The statement that "law is for humans" implies that law is a means to bring happiness to humans. To serve humans well, the law cannot simply spell out statutory articles but must also operate with empathy and courage (dare). The essence of progressive law lies in progressive thinking and action that frees it from the shackles of legal document texts, because ultimately, law is not for legal texts, but for human happiness and well-being. The method used in normative research with a problem-solving approach is the case approach. The decision regarding corruption committed by Susi Tur Handayani, where the corruption in question was not charged in the indictment, can be categorized as a progressive decision. Judges are not merely mouthpieces of the law, viewing statutory regulations textually, but need to develop a deep understanding of the articles contained within those statutory regulations. Keywords: Verdict, Indictment, Corruption Crime, Progressive Theory